2022
DOI: 10.1016/j.toxrep.2022.01.014
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of Nigella sativa seeds against monosodium glutamate-induced hepatic dysfunction in rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…N. Sativa administration protects hepatic tissue from the deleterious effects of toxic metals ( 27 ). In addition, N.sativa provided cytoprotectant by improving the histoarchitecture of the liver and decreasing the number of apoptotic cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N. Sativa administration protects hepatic tissue from the deleterious effects of toxic metals ( 27 ). In addition, N.sativa provided cytoprotectant by improving the histoarchitecture of the liver and decreasing the number of apoptotic cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that N. sativa treatment protects the rat liver from hepatic ischemia-reperfusion injury by increasing antioxidant enzymatic activities significantly ( 29 ). Furthermore, Through its antioxidant and anti-apoptotic properties, N. Sativa was effective in protecting against hepatotoxicity ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Catalase reduces oxidative stress and lipid peroxidation either by protecting the detoxifying enzymes by increasing the efficacy of Nicotineamide Dinucleotide Phosphate (NADPH) or by helping in the elimination of compounds that produce peroxidation in the cell membranes 58 . Since H 2 O 2 acts as a substrate for a specific reaction that generates highly hydroxyl radicals, it is believed that the primary role of catalase in cellular antioxidant defense mechanisms is to reduce the accumulation of H 2 O 2…”
Section: Discussionmentioning
confidence: 99%
“…NSS has an abundance of redox stabilizers, including thymoquinone, flavonoids, and terpenoids 11 . NSS boosts the transcript level of redox stabilizers 60 , and shifts the cell fate decisions to pro-survival events 61 . By elevating proliferating cell nuclear antigen, TQ stimulates cell multiplication, thereby enhancing the ability of cell to regenerate after tissue injury 62,63 .…”
Section: Discussionmentioning
confidence: 99%